2013
DOI: 10.1111/lcrp.12018
|View full text |Cite
|
Sign up to set email alerts
|

After innocence: Perceptions of individuals who have been wrongfully convicted

Abstract: Purpose Although it is easy to assume that individuals who have been wrongfully convicted are stigmatized, research has not systematically examined this issue. This research compares perceptions of individuals who have been wrongfully convicted to perceptions of offenders to investigate the stigma that wrongfully convicted persons report. Method Participants were randomly assigned to complete surveys regarding their attitudes, stereotypes, and discrimination tendencies towards one of three different groups: in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 62 publications
9
66
1
Order By: Relevance
“…In addition, Clow and Leach (2013) found that participants rated people who had been wrongly convicted as less friendly, respected, warm, and lazy than controls. Similarly, Thompson et al (2012) found that participants rated an exoneree as less competitive, confident, intelligent, warm, and good-natured than a transfer student.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, Clow and Leach (2013) found that participants rated people who had been wrongly convicted as less friendly, respected, warm, and lazy than controls. Similarly, Thompson et al (2012) found that participants rated an exoneree as less competitive, confident, intelligent, warm, and good-natured than a transfer student.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…Specifically, we predicted that participants would be more likely to perceive Daniel Cooper as guilty (Hypothesis 1), to rate him lower in both competence and warmth (Hypothesis 2), to express greater feelings of anger (Hypothesis 3), to express less feelings of pity (Hypothesis 4), and to report less willingness to offer government assistance (Hypothesis 5) in the false confession condition than in the mistaken eyewitness or jailhouse snitch conditions. Finally, based on previous stigma and wrongful conviction research (Clow & Leach, 2013;Thompson et al, 2012), we expected participants to rate Daniel Cooper higher in competence and warmth in the control condition than in each of the wrongful conviction conditions (Hypothesis 6).…”
Section: Current Studymentioning
confidence: 97%
See 2 more Smart Citations
“…A nascent body of research suggests that, despite their innocence, exonerees face stigma similar that of to actual offenders. Clow and Leach () found that students rated wrongfully convicted individuals as less warm, less friendly, and less respected than the average person and desired greater social distance from them. Moreover, they rated exonerees and actual offenders as equally trustworthy, competent, aggressive, and deserving of government assistance (e.g., job training, subsidized housing).…”
Section: Introductionmentioning
confidence: 99%